ทัศนะการจัดประสบการณ์ฝึกงานสำหรับนิสิตเทคโนโลยีการศึกษา - มนัส บุญประกอบ (จุฬาลงกรณ์มหาวิทยาลัย, 1982)
Proposes concept on arranging the teaching training experience for students on educational technology as teaching training is considered to be one of the necessitated and significant educational experience. Emphasizes that students who take major or minor on educational technology should be trained differently from students who take major or minor on other subjects, systematically the training system, focusing on steps for training, and skills necessary for training.